2020
DOI: 10.1186/s43014-020-00027-9
|View full text |Cite
|
Sign up to set email alerts
|

Finger millet porridges subjected to different processing conditions showed low glycemic index and variable efficacy on plasma antioxidant capacity of healthy adults

Abstract: Finger millet porridges (FMP), rich in nutrient and non-nutrient compounds have been used in the traditional food cultures in Asia. The aims of the study were to determine the effect of different processing conditions of finger millet grains on glycemic response, phenolic content and the antioxidant activities of FMP and to determine the short term and long term efficacy of its consumption on plasma antioxidant levels of healthy adults. Twelve types of FMP were prepared combining different processing condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Finger millet, foxtail millet, barnyard millet, and/or a mixture of millets (finger millet and little millet) were used in the 19 studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) that were included in one or more outcomes of meta-analysis. It was observed that consumption of milletbased food for a duration varying from 21 days to 4 months had a significant reducing effect on TC, triacylglycerol, VLDL-C, and/or LDL-C levels.…”
Section: Resultsmentioning
confidence: 99%
“…Finger millet, foxtail millet, barnyard millet, and/or a mixture of millets (finger millet and little millet) were used in the 19 studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) that were included in one or more outcomes of meta-analysis. It was observed that consumption of milletbased food for a duration varying from 21 days to 4 months had a significant reducing effect on TC, triacylglycerol, VLDL-C, and/or LDL-C levels.…”
Section: Resultsmentioning
confidence: 99%
“…The FRAP assay was carried out according to Kumari et al ., 20 with some modifications. Phenolic extracts (20 μL) and freshly prepared FRAP reagent (2.5 mL of 20 mmol L −1 iron(III) chloride hexahydrate, 25 mL of 300 mmol L −1 sodium acetate buffer, 2.5 mL of 10 mmol L −1 2,4,6‐Tris(2‐pyridyl)‐ S ‐triazine (TPTZ) in 40 mmol L −1 hydrochloric acid) were combined in a 96‐well microplate.…”
Section: Methodsmentioning
confidence: 99%
“…The ferric reducing power of phenolic extracts was measured according to Kumari et al, 14 with some modifications. Freshly prepared FRAP reagent contained 2.5 mL of 20 mmol/L iron chloride (III) hexahydrate, 25 mL of 300 mmol/L sodium acetate buffer, and 2.5 mL of 10 mM 2,4,6-tris(2-pyridyl)-s-triazine (TPTZ) diluted in 40 mM hydrochloric acid.…”
Section: Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 99%